2015
DOI: 10.1371/journal.pone.0132574
|View full text |Cite
|
Sign up to set email alerts
|

Light-Dependent Aerobic Methane Oxidation Reduces Methane Emissions from Seasonally Stratified Lakes

Abstract: Lakes are a natural source of methane to the atmosphere and contribute significantly to total emissions compared to the oceans. Controls on methane emissions from lake surfaces, particularly biotic processes within anoxic hypolimnia, are only partially understood. Here we investigated biological methane oxidation in the water column of the seasonally stratified Lake Rotsee. A zone of methane oxidation extending from the oxic/anoxic interface into anoxic waters was identified by chemical profiling of oxygen, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
158
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 137 publications
(177 citation statements)
references
References 64 publications
19
158
0
Order By: Relevance
“…Concurrent with the present work, Oswald et al (2015) found the presence of aerobic methane oxidizers in the anoxic zone of Lake Rot, a highly eutrophic, dimictic lake situated north of Lucerne (Switzerland), while no known groups of anaerobic methane oxidizing archaea were found in the water column. Laboratory incubations with water samples taken from the zone below the oxycline revealed that irradiation with light stimulated methane oxidation significantly, which suggests that methane oxidation in the virtually anoxic water column is tightly coupled to oxygenic primary production.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Concurrent with the present work, Oswald et al (2015) found the presence of aerobic methane oxidizers in the anoxic zone of Lake Rot, a highly eutrophic, dimictic lake situated north of Lucerne (Switzerland), while no known groups of anaerobic methane oxidizing archaea were found in the water column. Laboratory incubations with water samples taken from the zone below the oxycline revealed that irradiation with light stimulated methane oxidation significantly, which suggests that methane oxidation in the virtually anoxic water column is tightly coupled to oxygenic primary production.…”
Section: Introductionsupporting
confidence: 88%
“…The uncorrected oxygenic as well as the anoxygenic PP rates indicate that primary producers in the aphotic zone are still capable of PP in the presence of light. This potential for oxygenic PP was also confirmed by Oswald et al (2015) who observed a strong stimulation of methane oxidation in samples taken between 9 and 11 m on the 5th of August when they were irradiated by light in the laboratory (see their Fig. 3).…”
Section: Phototrophy Under Low Light Conditions In Lake Rotsupporting
confidence: 74%
See 3 more Smart Citations